2015
DOI: 10.1002/mrm.25661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of white matter microstructure on phase and susceptibility maps

Abstract: Purpose: To investigate the effects on quantitative susceptibility mapping (QSM) and susceptibility tensor imaging (STI) of the frequency variation produced by the microstructure of white matter (WM). Methods: The frequency offsets in a WM tissue sample that are not explained by the effect of bulk isotropic or anisotropic magnetic susceptibility, but rather result from the local microstructure, were characterized for the first time. QSM and STI were then applied to simulated frequency maps that were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 38 publications
4
62
0
Order By: Relevance
“…Susceptibility contrast in the thalamus can be affected by myelin content. 45 However, due to the TE-dependent and anisotropic effect of myelinated fibers and white matter microstructure on measured susceptibility, 46,47 histological correlation with myelin staining is not straightforward. Further, focal mineralization in the lesions can be accompanied by varying degrees of demyelination, thus the contribution of myelin to QSM contrast in thalamic gray matter nuclei is expected to be weak in comparison to the effects of pathological iron and calcium accumulations.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility contrast in the thalamus can be affected by myelin content. 45 However, due to the TE-dependent and anisotropic effect of myelinated fibers and white matter microstructure on measured susceptibility, 46,47 histological correlation with myelin staining is not straightforward. Further, focal mineralization in the lesions can be accompanied by varying degrees of demyelination, thus the contribution of myelin to QSM contrast in thalamic gray matter nuclei is expected to be weak in comparison to the effects of pathological iron and calcium accumulations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar contrast can be obtained using Quantitative Susceptibility Mapping (QSM), where phase data are processed to extract the underlying magnetic susceptibility () distribution, resulting in a novel quantitative anatomical contrast of an intrinsic physical tissue property (de Rochefort et al, 2010). Fiber direction, iron and/or myelin are known to influence the susceptibility contrast, although the exact origin of this contrast is not fully understood (Wharton and Bowtell, 2015). Phase and susceptibility contrasts are based on spatial susceptibility distribution.…”
Section: High-field Short-te Mr Imagingmentioning
confidence: 99%
“…Phase and susceptibility contrasts are based on spatial susceptibility distribution. Recently it was suggested that white matter structure such as axonal microstructure may also have an impact on phase and susceptibility contrasts (Wharton and Bowtell, 2015). Both of these MR modalities are of great interest in the field of perinatal brain injury since it is frequently associated with myelination impairment and neuronal/axonal disease (Ferriero, 2004;Volpe, 2009).…”
Section: High-field Short-te Mr Imagingmentioning
confidence: 99%
See 2 more Smart Citations